Proyecto de factibilidad para la creación de una empresa de lavado y lubricado de vehículos en el cantón Catamayo, Provincia De Loja. - Morocho Medina, José Alberto (2014)
The increase of the fleet in the canton Catamayo has allowed new washers and lubricadoras also believe, given this is so need to create a new company that offers the service in the Canton province of Loja Catamayo, quality service arises care to ensure vehicle customers, in order to be released to customers and earn a higher position in the market, in order to be recognized among consumers; himself to avoid irreparable damage to the environment with its pollution and waste wash car lubricated, so that must be controlled to create a new service station car wash and lubricated so that it meets all conditions set out in the current legal framework, and has the appropriate technology to provide a differentiated service in Canton. This proposal relates to the study of a proposed feasibility of implementing a machine lubricator vehicle and a water reclamation system in the city, the purpose of this project is to provide a high quality service in less time and contribute to society with the lifesaving liquid. The survey results identified an acceptance of 89%, with an annual demand according to 6552 installed services vehicles washed and lubricated capacity, taking into account that for the first year will work with 80% of the capacity, giving a total of 5242 washing and lubrication services for vehicles, with a total of 32 services a day giving a total income for the first year of $ 217,375.57; so it is important to note that in the following years increased services will be held 5% annually to reach 99% of the installed capacity of the plant in the last year of life of the project. The car washer and lubricator will be located in the Streets: Beltway and Bolivar Avenue, will have 8 people to operate and comply with standards established by law. The initial investment for the implementation of the proposal will be $ 42,928.80 of which will have equity of $ 22,928.80 and $ 20,000 financed by credit extended bank building in the city, at an interest rate of 14 % per year within 2 years. In Economic Evaluation of the VAN $ 107,040.61 IRR of 91.8% above the discount rate of 14%, the payback period of the investment will be 1 year, 1 month and 4 days; the cost-benefit ratio indicates that for every dollar invested company will use $ 0.40 cents; with regard to sensitivity analysis indicates that the project supports increased costs to 14.22% and a decrease in revenue of up to 10,157%. The results demonstrate the feasibility of implementing a lubricated wash company vehicles in the canton Catamayo; therefore has demonstrated the feasibility of the proposal and the start of the activities recommended